The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ef3017915
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Interfacial Interactions among Crude Oil–Brine–Sandstone Rock–CO2 by Contact Angle Measurements

Abstract: Wettability plays a crucial role on the performance of enhancing oil recovery techniques because of its effect on fluid saturations and flow behavior in porous medium. This study is directed toward determining contact angles (i.e., wettability) in systems with carbon dioxide, brine, and an oil-saturated rock system. Two situations are considered: Rock system I is partially water-wet, whereas rock system II is effectively oil-wet. Contact angles have been determined experimentally as a function of brine salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 45 publications
8
53
0
Order By: Relevance
“…Furthermore, wettability alteration by CO 2 dissolution in brine has already been investigated for the systems of CO 2 -water-coal 9-11 , CO 2 -brine-Mica 12, 13 , CO 2 -brine-Quartz 12, 14 , CO 2reservoir brine-reservoir rock [15][16][17][18] and CO 2 -water-glass 19,20 ; however, very limited study focus on the wettability alteration of oil-brine-rock system with dissolution of CO 2 21 . Grape et al 22 performed imbibition tests involving CO 2 -enriched water (carbonated water).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, wettability alteration by CO 2 dissolution in brine has already been investigated for the systems of CO 2 -water-coal 9-11 , CO 2 -brine-Mica 12, 13 , CO 2 -brine-Quartz 12, 14 , CO 2reservoir brine-reservoir rock [15][16][17][18] and CO 2 -water-glass 19,20 ; however, very limited study focus on the wettability alteration of oil-brine-rock system with dissolution of CO 2 21 . Grape et al 22 performed imbibition tests involving CO 2 -enriched water (carbonated water).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that CO 2 -EOR and successful CO 2 sequestration are largely controlled by the interfacial characteristics among the injected CO 2 , the reservoir crude oil, the brine and the rock. [6][7][8][9] The interfacial tension (IFT) under high pressure directly relates to the capillary pressure, the maximum storage height of CO 2 , and the flow behaviors in porous media. [9][10][11] If the reservoir pressure is higher than the minimum miscibility pressure (MMP), CO 2 and oil become completely miscible 12 and they contact with brine together at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…IFEMA Madrid, Spain, 1-4 June 2015 1-4 June 2015 | IFEMA Madrid the measurements (Ameri et al 2013, Shojai Kaveh et al 2014. When the aqueous phase is not completely saturated with CO 2 , the injectivity and the gas distribution in the reservoir are not only influenced by the rock properties but also by the diffusion of CO 2 into the aqueous phase (Shojai Kaveh et al 2011, Shojai Kaveh et al 2012).…”
Section: Introductionmentioning
confidence: 99%